Fuel poverty and financial literacy: Evidence from Irish home owners - Miguel Angel Tovar Rea\~nos; John A. Curtis; Arya Pillai; David Meier (The Economic and Social Research Institute (ESRI), 2023)
Fuel poverty is a condition that is distressing families in Europe and elsewhere. One of its drivers is low energy efficiency levels. Some research indicates that financial literacy can help achieve higher levels of energy efficiency. We use data from a survey of Irish home owners to analyse how financial literacy can affect the decision making process when adopting measures to reduce the burden imposed by high energy prices. We also analyse the role of financial preferences in current levels of energy efficiency, barriers to accessing energy efficiency retrofit grants and the relationship between fuel poverty and financial literacy. We find only a very weak association between financial literacy and fuel poverty across a set of different metrics. Household income is very strong strongly associated with both fuel poverty and energy effi-ciency. Our findings provide the first empirical evidence of the association between financial literacy and fuel poverty, and that the administrative burden associated with accessing energy efficiency retrofit grants represents a substantial barrier.
Keywords: 330